Flavor education and training in olfactory dysfunction: a pilot study - Besser, Gerold; Oswald, Michaela M.; Liu, David T.; Renner, Bertold; Mueller, Christian A. (European Archives of Oto-Rhino-Laryngology, 2020)
Purpose: Olfactory training is recommended in olfactory dysfunction (OD) showing promising results. OD patients frequently ask for training modifications in the hope of a better outcome. Also, a lack of knowledge of the flavor system is evident. This investigation sought to implement flavor education (FE) and encourage patients to experience flavors in terms of a flavor training (FT). Methods: In included patients (n = 30), OD was either of postinfectious (86.7%) or posttraumatic (13.3%) cause. Chemosensory abilities were tested orthonasally (using Sniffin Sticks = TDI) and retronasally (using the Candy Smell Test = CST). Key points of flavor perception were demonstrated in an educative session. Subjects were instructed to consciously experience flavors out of a list of 50. Effects of FT were explored in two groups (group A and B), with group B starting FT 17 weeks later. Results: FE was appreciated and drop-out rate stayed very low (one participant). Compliance was high and 30.4 ± 12.9 flavors were tried. Overall TDI scores improved in 10 patients (6 group A, 4 group B) in a clinically significant way (> 5.5). For group A (starting FT earlier) rm-ANOVA showed a significant effect of session (timepoint) on CST (p < 0.01). Conclusion: Flavor education is demonstrated as feasible and appreciated in a clinical setting. FT seems to be a welcomed second-line therapy in patients with olfactory dysfunction. This study shows beneficial trends of FT; however, further studies with larger sample sizes and standardized training protocols are needed.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Anosmia; Hyposmia; Olfactory training; Quality of life; Retronasal